Opus Marina Držića u kontekstu književnog turizma (mogućnosti razvijanja književnog turizma na primjeru recepcije Marina Držića) - Bakija, Katja; Konsuo Kuzmanić, Marija (SlavVaria, 2026)
The Works of Marin Držić in the Context of Literary Tourism (Possibilities for Developing Literary Tourism Based on the Reception of Marin Držić). This paper seeks to explore the potential of literary tourism through the reception of the works of Marin Držić, the great Croatian playwright whose timeless and still relevant messages have enriched both Croatian and European literature. His enigmatic and colorful biography continues to intrigue readers and directors, inviting new interpretations. Literary tourism, considered a branch of cultural tourism, involves visiting places and events associated with writers and their works. This paper analyzes the current state and critically examines Držić within the framework of literary tourism theory. This paper also seeks to offer new ideas in literary tourism, using the example of knowing and interpreting the life and work of the Dubrovnik, Croatian and European comedy writer Marin Držić.